1998
DOI: 10.1007/s001980050102
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Measurements of Proximal Phalanges in Polish Early Postmenopausal Women

Abstract: The aim of this cross-sectional study was to evaluate skeletal status in Polish early postmenopausal women using ultrasound measurement at the proximal phalanges of the hand. We assessed the ability of the method to discriminate between healthy and osteoporotic individuals, the influence of age and menopause on ultrasound values, the impact of hormone replacement therapy and the relationships between ultrasound measurement and type of fracture. Five hundred and three early postmenopausal women were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…CV% was established on the basis of 75 bone scans with repositioning of the device caliper (5 measurements in each subject). The detailed methodology was described by Pluskiewicz and Drozdzowska [20].…”
Section: Qus Measurementmentioning
confidence: 99%
“…CV% was established on the basis of 75 bone scans with repositioning of the device caliper (5 measurements in each subject). The detailed methodology was described by Pluskiewicz and Drozdzowska [20].…”
Section: Qus Measurementmentioning
confidence: 99%
“…5,27,32,33,[35][36][37] Multi-site quantitative ultrasound has demonstrated differing peak bone mass for different sites, with the weight bearing sites tending to peak earlier and have a lower rate of bone loss postmenopausally. 32,33 Studies evaluating premenopausal age related changes salud pública de méxico / vol.…”
Section: Age-related Changesmentioning
confidence: 99%
“…51, suplemento 1 de 2009 Knapp KM at the phalanges using the DBM-sonic have also found age-related bone loss premenopausally. 4,5 Correlation with DXA The correlation of QUS measurements with BMD has generally yielded weak to moderate correlations, particularly when peripheral QUS measurement sites have been correlated with axial BMD. 7,33 Faulkner et al found correlations ranging from 0.26-0.63 for calcaneal QUS and DXA of the spine, hip, forearm and whole body.…”
Section: Age-related Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The phalangeal quantitative ultrasound (QUS) measurement was introduced more than a decade ago and has been validated in various clinical studies [6][7][8][9]. This technique, by measuring the amplitude-dependent speed of sound, may provide useful information not only on bone mass but also on bone tissue architecture and elasticity.…”
Section: Introductionmentioning
confidence: 99%